A modified predictive model for colour changes in French fries during frying - Siti Nabihah, Othman; Norazaliza, Mohd Jamil (IOP Publishing, 2021)
During frying, heat and mass transfer phenomena happen and cause the physiochemical changes that affect the colour of french fries. Moisture content, oil content, and colour are important quality parameters in frying french fries, while temperature, frying time, and sample thickness will affect the french fries. In this study, we developed a modifiedmathematical model for colour changes of French fries during frying. The colour changes were formulated using a first-order ordinary differential equation that was solved using the 4th order Runge-Kutta method in the MATLAB software. The formulation for rate constant was modified using the Arrhenius equation and the sum squared error (SSE) of the proposed model was compared with the SSE of existing models. The colour was evaluated based on two parameters which are oil temperature (150°C,170°C,190°C) during frying and sample thickness (5 mm,10 mm,15 mm) of french fries. The results showed that incorporating the factor of moisture into the model provides a better prediction of lightness and yellowness of french fries during frying. Overall, we conclude that moisture plays a significant role in the colour changing of french fries.